Country Partnership Framework for the Republic of Colombia for the Period FY16-21 - World Bank Group (World Bank, Washington, DC, 2016)
The WBG’s Colombia Systematic Country Diagnostic (SCD) analyzed key constraints and opportunities that will impact Colombia’s development in the context of three defining country characteristics. They include uneven territorial development, a long standing armed conflict and a growth process led by extractive industries. The Colombia Country Partnership Framework (CPF) proposes to address these complex development challenges with a flexible, six-year (FY16-21) engagement that builds on the strong and trusted client relationship established over recent years. On the basis of client country demand, the development challenges highlighted in the SCD, and World Bank Group (WBG) comparative advantage, the CPF focuses on eight critical objectives to guide WBG engagement over the CPF period. These objectives are organized within three pillars of engagement: (a) fostering balanced territorial development; (b) enhancing social inclusion and mobility through improved service delivery; and (c) supporting fiscal sustainability and productivity. Cutting across all pillars, the CPF aims to ‘assist in constructing the peace’ in response to Colombia’s historic opportunity to reach a Peace Accord after more than 50 years of conflict.